PENGARUH PEMBERIAN HORMON TIROKSIN PADA PAKAN TERHADAP PERTUMBUHAN IKAN MASKOKI (Carrasius auratus) Effect of Giving Thyrocsine Hormone in Feed and Growth of Maskoki (Carrasius auratus) - Dian Roy Nugraha Sembiring; Eri Yusni; Indra Lesmana (AQUACOASTMARINE, 2015)
Maskoki is ornamental fish and high ecomonic value. The aim of this study using thyrocsine compared on the fish consumption. Effect of growth in ornamental fish depend for the hormone were give. The result was higher of body weight 5.84 g followed 7.24 cm length growt, 2.19% Spesific Growt Rate (SGR), 0.05 g Daily Weigth Gain (DWG), 0.29 g Feed Convertion Ratio (FCR), 96.67 % Survival Rate (SR) with thyrocsine hormone of 25 mg, compared the other fish was lowest body weight 4,74 g followed 6,55 cm length growt, 0.74 Spesific Growt Rate (SGR), 0.02 g Daily Weight Dain (DWG), 0.23 g Feed Convertion Ratio (FCR), and 93.33 % Survival Rate (SR) with thyrocsine hormone of 10 mg.Keywords : Fish, Hormone, Growth, SGR, DWG.